Komparasi Pendidikan Karakter Indonesia dan Jepang (Analisis terhadap Landasan, Pendekatan, dan Problematikanya) - Syamsurrijal, Arif (Prodi PAI STAI Sumatera Medan, 2021)
This study aims to analyze the comparison of the implementation of character education between Indonesia and Japan. The focus of the study is on three things, namely the basis, approach, and problems of character education in two countries. The research method used is a qualitative research method using a library approach or better known as library research. The data sources of this research come from research results, books, or government policies related to character education in the two countries. The results of the study explain that the basis of character education in Indonesia is the ideology of the state, customs and culture, religious values, government rules and policies. Likewise, in Japan the basis of character education is in the form of cultural values, state ideology, and government policy rules. Approaches to character education in Indonesia include the value inculcation approach, the value clarification approach, the learning approach to action, exemplary, and habituation. Meanwhile, in Japan, among other things, the approach tends to be habituation, for Japanese people, characters are not taught but are used to it. Character problems in Indonesia and Japan are not too different around juvenile delinquency, free sex, vandalism and thuggery. The difference in stress levels in Japan affects the character of the younger generation.